Understanding the benefits and challenges of first‐line cyclin‐dependent kinases 4 and 6 inhibitors in advanced breast cancer among postmenopausal women. Issue 4 (10th November 2019) - Azim, Hamdy A.; Dawood, Shaheenah; El‐Saghir, Nagi; Kassem, Loay; Azim, Hatem A.
Abstract: Endocrine therapy (ET) has been regarded for many years as the standard treatment for patients with hormone receptor‐positive (ER+), HER2‐negative (HER2−) advanced breast cancer (ABC) without visceral crisis. However, the efficacy of single‐agent ET is constrained by the development of resistance, attributed to alterations in several intracellular signaling pathways, including those related to cell cycle dysregulation. The cyclin‐dependent kinases 4 and 6 (CDK4/6) are principal regulators of cell cycle progression from the G1‐phase into the DNA synthesis (S)‐phase. In vitro inhibition of CDK4/6 activity has potent antiproliferative properties against luminal breast cancer cell lines, which are enhanced when combined with traditional ET. This has led to a substantial interest in targeting this pathway to overcome endocrine resistance in the clinic. Three selective CDK4/6 inhibitors (palbociclib, ribociclib, and abemaciclib) have been approved as first‐line therapy in combination with an aromatase inhibitor, or fulvestrant in the case of ribociclib in patients with ER+/HER2− ABC. To date, there is no clue as to which subgroup of patients might benefit most from these combinations. Here, we outline some of the established approaches to overcome endocrine resistance, with special emphasis on the unique mechanism of action of CDK4/6 inhibitors.